Vocational education and training - an engine for growth and a vehicle for social inclusion? - Nilsson, Anders [Verfasser] (My University, 2010)
"Vocational education and training (VET) has in recent years enjoyed a revival for two major reasons. Firstly, it is regarded as a suitable means of promoting economic growth. Secondly, it is seen as a potentially powerful tool for fostering social inclusion. In this review, these assumed effects are critically examined on the basis of the vastly expanding literature in the field. Evidence of the productivity-enhancing effects of VET at company level is quite solid, but evidence of the effect on overall economic growth is far from conclusive. The effects on social inclusion are uncertain because reform of VET systems has not been sufficient and because it has proved difficult to bring about the necessary institutional change. The review identifies policy implications and makes some suggestions for future research." (Autorenreferat, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 2 Trends & Entwicklungen; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 2.4 Sozialer Wandel; I 2.2 Europa; Berufsbildung; Berufsbildungssystem; Reform; Wirkung; Wirtschaftsentwicklung; Soziale Integration; Europa